Analysis of the Presence of Pathogenic Bacteria Escherichia coli and Salmonella sp. in Organic Fertilizer - Harvianti, Yuniar; Permatasari, Atikah; Yulianti, Nurhasanah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Organic fertilizers are widely used in agriculture as an environmentally friendly alternative to improve soil fertility and crop productivity. However, their safety remains a concern due to the potential contamination by pathogenic bacteria, particularly Escherichia coli and Salmonella sp., which may pose risks to human health. This study aimed to analyze the presence of E. coli and Salmonella sp. in solid organic fertilizer samples based on the requirements of the Indonesian National Standard (SNI 7763:2024). Laboratory analyses were conducted at the Balai Standardisasi dan Pelayanan Jasa Industri (BSPJI) Palembang using standard microbiological methods, including presumptive and confirmatory tests, followed by Most Probable Number (MPN) estimation. The results confirmed the presence of E. coli colonies with a characteristic metallic green sheen on Eosin Methylene Blue Agar (EMBA), with an estimated concentration of 30 MPN/g, still below the SNI threshold of 100 MPN/g. In contrast, Salmonella sp. was not detected in the samples, as shown by negative growth on Salmonella Shigella Agar (SSA), with an estimated value of <3.0 MPN/g. These findings indicate that the tested organic fertilizer samples comply with microbiological safety standards, suggesting that the production and handling processes were adequate to minimize pathogenic contamination. Continuous monitoring and strict adherence to hygienic practices are recommended to ensure the consistent quality and safety of organic fertilizers in agricultural applications.